2020
DOI: 10.3390/molecules25133095
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Capacity of Vitamin B12 and Creatinine on Highly-Mesoporous Activated Carbons Obtained from Lignocellulosic Raw Materials

Abstract: Enterosorbents are widely-used materials for human body detoxification, which function by immobilizing and eliminating endogenous and exogenous toxins. Here, activated carbons, obtained from the lignocellulosic raw vegetal materials of indigenous provenance, have been studied. Walnut shell and wood from local species of nuts and apple-trees were carbonized, and further activated at high temperatures with water vapors in a rotary kiln. A second activation was carried out, in a fluidized bed reactor, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The results indicate that RAC has a graphitelike structure, which is consistent with the XRD analysis results [40]. The peaks at 288.58 eV belonged to -COOH, which can form a hydrogen bond with creatinine and uric acid [38]. The N 1 s spectrum in Fig.…”
Section: Structure and Morphological Analysis Of Racsupporting
confidence: 85%
See 3 more Smart Citations
“…The results indicate that RAC has a graphitelike structure, which is consistent with the XRD analysis results [40]. The peaks at 288.58 eV belonged to -COOH, which can form a hydrogen bond with creatinine and uric acid [38]. The N 1 s spectrum in Fig.…”
Section: Structure and Morphological Analysis Of Racsupporting
confidence: 85%
“…2C). The characteristic absorption peak at 3435 and 1625 cm −1 was attributed to the stretching vibration of the hydroxyl group, carbonyl, and the skeletal vibration of aromatic C = C bonds [37], while the adsorption bands of 2930 and 2853 cm −1 could be attributed to -CH 2 and -CH 3 groups [38]. These results indicated that the surface of the sample was rich oxygen-containing functional groups, which might form hydrogen bonds with creatinine and uric acid.…”
Section: Structure and Morphological Analysis Of Racmentioning
confidence: 85%
See 2 more Smart Citations
“…The simple method of preparation of mesoporous activated carbons is a direct pyrolytic carbonization, followed by physical activation with gaseous agents (carbon dioxide, water vapour) [ 36 ]. To improve the mesoporous structure of the final product the second activation is advisable in a fluidized bed reactor [ 37 ]. The synthesis process conditions such as type of raw material, temperature, time and activation agent affect development of the internal structure of adsorbents.…”
Section: Introductionmentioning
confidence: 99%